Titanium alloy and preparation method thereof

By covering TiB2, polyamine and graphene oxide layers on the surface of the titanium alloy ball, and using rare earth elements to seize the oxide film, the problem of difficulty in taking into account the strength and toughness of the titanium alloy powder after injection molding is solved, the high strength and toughness of the titanium alloy are achieved, and the sintering density is improved.

CN119663050AActive Publication Date: 2025-03-21ZHEJIANG ASIA GENERAL SOLDERING & BRAZING MATERIAL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411565216.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-21
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

After injection molding, existing titanium alloy powders are difficult to take into account both strength and toughness. At the same time, the high activity of titanium alloy leads to oxidation during sintering, forming impurity phases, and reducing density and toughness.

Method used

By sequentially covering the TiB2 layer, the polyamine layer and the graphene oxide layer on the surface of the titanium alloy ball, the graphene oxide layer contains cerium elements to form a specific powder structure, improve the interface bonding between the titanium alloy matrix and graphene, and seize the oxide film through rare earth elements during sintering, promoting sintering and refining grains.

Benefits of technology

It realizes that the titanium alloy has good strength and toughness after injection molding, while improving the sintering density and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119038860000071
    Figure BDA0005119038860000071
  • Figure BDA0005119038860000081
    Figure BDA0005119038860000081
Patent Text Reader

Abstract

The invention discloses a titanium alloy. The titanium alloy is obtained by injection molding of titanium alloy powder. The titanium alloy powder comprises a titanium alloy ball, a TiB2 layer, a polyamine layer and a graphene oxide layer, the surface of the titanium alloy ball is sequentially coated with the TiB2 layer, the polyamine layer and the graphene oxide layer, and the graphene oxide layer contains cerium. The invention also discloses a preparation method of the titanium alloy, which comprises the following steps: mixing titanium alloy powder with a binder, carrying out injection molding, degreasing, carrying out vacuum sintering at 1000-1100 DEG C for 2-3 hours, cooling to room temperature, carrying out solid solution at 700-720 DEG C for 40-60 minutes, carrying out air cooling to room temperature, carrying out heat preservation at 450-470 DEG C for 3-3.5 hours, and then carrying out air cooling to room temperature to obtain the titanium alloy. The titanium alloy disclosed by the invention keeps good toughness while having good strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, and in particular to a titanium alloy and a preparation method thereof. Background Art

[0002] Titanium and titanium alloys have excellent properties such as low density, high specific strength, good plasticity, heat resistance and corrosion resistance. They can be widely used as a new type of structural material in aviation, aerospace, biomedicine, chemical industry, shipbuilding, automobile and other fields, especially in the aviation field. Although titanium is abundant in the earth's crust, its high melting point, high strength and high chemical activity make it difficult to machine, resulting in the high production cost of titanium alloy products. In addition, the titanium alloy structural parts that can be machined are relatively simple. Due to the limitations of the processing method, most of their design schemes cannot bring out the best performance of the material. Based on this background, metal powder injection molding technology with high raw material utilization, mass production and low production cost has become one of the most effective technical means for the preparation of titanium and titanium alloy parts.

[0003] The general operating process of powder injection molding technology is: first, the prepared powder and binder are mixed and granulated into granular feed, and then the feed is formed into a specific shape of product green body on the injection molding machine, and then degreasing and sintering are carried out to obtain the product with the required performance.

[0004] However, the strength and toughness of titanium alloys obtained by injection molding using existing titanium alloy powders cannot be achieved at the same time; and during sintering, titanium metal is highly active and easily oxidized at around 400°C to generate impurity phases such as titanium oxide, which will further reduce the sintered relative density, and as the oxygen content increases, the toughness of the titanium alloy will further deteriorate. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a titanium alloy and a preparation method thereof. The present invention performs structural design on titanium alloy powder from multiple aspects such as improving the interface bonding strength between graphene and titanium alloy, improving the sintering density, refining the grains and alloy structure, so that the titanium alloy obtained by injection molding has good strength while maintaining good toughness.

[0006] The present invention provides a titanium alloy, which is obtained by injection molding of titanium alloy powder;

[0007] The titanium alloy powder comprises: a titanium alloy ball and a TiB2 layer, a polyamine layer and a graphene oxide layer sequentially coated on the surface of the titanium alloy ball, and the graphene oxide layer contains cerium element.

[0008] Preferably, the titanium alloy ball is a TC4 titanium alloy ball, wherein the TC4 titanium alloy ball contains 0.2-0.4wt% Nd.

[0009] Adding an appropriate amount of Nd to the titanium alloy ball can capture oxygen in the titanium alloy during sintering, purify the matrix, and form nano rare earth oxides to refine the grains and the internal structure of the titanium alloy, thereby improving the strength and toughness of the titanium alloy.

[0010] The raw materials of the TC4 titanium alloy ball include, by weight percentage: Al 5.8-6.0%, V 4.0-4.2%, O 0.15-0.18%, Nd 0.2-0.4%, C≤0.10, N≤0.05, H≤0.015, and the balance is Ti and unavoidable impurities.

[0011] Preferably, the polyamine is at least one of diethylenetriamine and triethylenetetramine.

[0012] Preferably, the average particle size of the titanium alloy powder is 15-25 μm.

[0013] Preferably, in the process of preparing titanium alloy powder, titanium alloy balls are mixed with TiB2 and ball milled to obtain intermediate ball 1; intermediate ball 1 is mixed with a polyamine aqueous solution and allowed to react to obtain intermediate ball 2; intermediate ball 2 is mixed with a graphene oxide aqueous solution and electrostatically assembled to obtain intermediate ball 3; intermediate ball 3 is mixed with an aqueous solution containing cerium ions, electrostatically adsorbed, and vacuum dried to obtain titanium alloy powder.

[0014] The aqueous solution containing cerium ions may be an aqueous solution of cerium chloride, an aqueous solution of cerium nitrate, or the like.

[0015] In the present invention, TiB2 whiskers are loaded on the surface of a titanium alloy ball by a ball milling method to obtain an intermediate ball 1. The hydroxyl groups on the surface of the intermediate ball 1 can be chemically bonded with polyamines to form a positively charged polyamine layer, which is then electrostatically assembled with negatively charged graphene oxide to form a negatively charged graphene oxide layer, which is then electrostatically assembled with Ce 3+ Electrostatic adsorption is performed to fix the cerium element in the graphene oxide layer to obtain titanium alloy powder.

[0016] The specific structure of the above-mentioned titanium alloy powder can avoid the problem of easy oxidation of the titanium alloy surface, and during injection molding and sintering, TiB2 whiskers can form a network structure on the surface of the titanium alloy ball, and polyamine and graphene oxide form a TiC-coated graphene structure, which is tightly connected with the network structure of TiB2 whiskers, thereby improving the interface bonding force between the titanium alloy matrix and the graphene. This structure can improve the load transfer between the titanium alloy matrix and the graphene, greatly improving the strength and toughness of the titanium alloy; and TiB2 can further refine the alloy structure and improve the mechanical strength; in addition, the rare earth cerium fixed in the graphene oxide layer can capture oxygen in the oxide film on the surface of the titanium alloy during sintering, eliminate the oxide film, promote the sintering of the titanium alloy, and improve the sintering density, and the fine high-melting-point rare earth oxides formed can refine the grains, thereby further improving the mechanical properties of the titanium alloy.

[0017] Preferably, the weight ratio of the titanium alloy ball to TiB2 is 10:0.05-0.1.

[0018] Preferably, the ball milling speed is 100-150 rpm, and the ball milling time is 3-4 h.

[0019] Preferably, the reaction is allowed to stand at room temperature for 0.5-1 h.

[0020] Preferably, the electrostatic assembly is performed at room temperature for 0.5-1 h.

[0021] Preferably, the electrostatic adsorption is carried out at room temperature for 0.5-1 h.

[0022] Preferably, the mass fraction of the polyamine aqueous solution is 1-2 wt %.

[0023] Preferably, the mass fraction of the graphene oxide aqueous solution is 0.4-0.6wt%.

[0024] Preferably, in the aqueous solution containing cerium ions, the concentration of cerium ions is 0.02-0.04 mol / l.

[0025] The present invention also proposes a preparation method of the above-mentioned titanium alloy, comprising the following steps: mixing titanium alloy powder with a binder, injection molding, degreasing, vacuum sintering at 1000-1100°C for 2-3h, cooling to room temperature, solutionizing at 700-720°C for 40-60min, air cooling to room temperature, then keeping warm at 450-470°C for 3-3.5h, and then air cooling to room temperature to obtain a titanium alloy.

[0026] The present invention selects appropriate sintering process and heat treatment process, which can further refine the alloy structure and promote the interactive and tight connection between the TiB2 network structure and the TiC-coated graphene, thereby further improving the mechanical properties of the titanium alloy.

[0027] Beneficial effects:

[0028] The titanium alloy powder of the present invention can, on the one hand, avoid the problem of easy oxidation of the titanium alloy surface; on the other hand, during injection molding and sintering, the TiB2 whiskers can form a mesh structure on the surface of the titanium alloy ball, and the polyamine and graphene oxide form a TiC-coated graphene structure, which is interactively and tightly connected with the mesh structure of the TiB2 whiskers, thereby improving the interface bonding force between the titanium alloy matrix and the graphene. This structure can improve the load transfer between the titanium alloy matrix and the graphene, thereby greatly improving the strength and toughness of the titanium alloy;

[0029] In addition, the rare earth cerium fixed in the graphene oxide layer can capture oxygen in the oxide film on the surface of the titanium alloy during sintering, eliminate the oxide film, promote the sintering of the titanium alloy, and improve the sintering density. It can also cooperate with the Nd inside the titanium alloy ball to refine the grains and alloy structure through the mutual cooperation of the fine rare earth oxides formed inside and outside the titanium alloy ball, thereby further improving the mechanical properties of the titanium alloy.

[0030] The present invention designs the structure of titanium alloy powder from multiple aspects such as improving the interface bonding strength between graphene and titanium alloy, improving the sintering density, refining the grains and alloy structure, so that the titanium alloy obtained by injection molding has good strength while maintaining good toughness. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is described in detail below through specific embodiments.

[0032] Example 1

[0033] A titanium alloy obtained by injection molding of titanium alloy powder;

[0034] The titanium alloy powder comprises: a TC4 titanium alloy ball and a TiB2 layer, a polyamine layer, and a graphene oxide layer sequentially coated on the surface of the TC4 titanium alloy ball, wherein the graphene oxide layer contains cerium; the average particle size of the titanium alloy powder is 15 μm;

[0035] The raw materials of TC4 titanium alloy ball include by weight percentage: Al 5.9%, V 4.1%, O 0.17%, Nd0.2%, C≤0.10, N≤0.05, H≤0.015, and the balance is Ti and unavoidable impurities;

[0036] In the process of preparing titanium alloy powder, TC4 titanium alloy ball and TiB2 are mixed at a weight ratio of 10:0.05, and ball milled at a speed of 150 rpm for 3 hours using a stainless steel ball at a ball-to-material ratio of 4:1 to obtain intermediate ball 1; intermediate ball 1 is mixed with a 2wt% diethylenetriamine aqueous solution, allowed to react at room temperature for 0.5h, taken out and washed with water to obtain intermediate ball 2; intermediate ball 2 is mixed with a 0.6wt% graphene oxide aqueous solution, allowed to stand at room temperature for electrostatic assembly for 0.5h, taken out and washed with water to obtain intermediate ball 3; intermediate ball 3 is mixed with a 0.04mol / l cerium chloride aqueous solution, allowed to stand at room temperature for electrostatic adsorption for 0.5h, taken out and washed with water, and vacuum dried to obtain titanium alloy powder.

[0037] The preparation method of the above-mentioned titanium alloy includes the following steps: taking titanium alloy powder and a binder (the formula of the binder is: 83% PW+15% LDPE+2% SA by weight percentage) in a weight ratio of 1:1 and mixing them to obtain a granular feed, followed by injection molding, solvent degreasing, vacuum sintering for 3 hours in a 1000°C vacuum sintering furnace, cooling to room temperature, solutionizing at 700°C for 60 minutes, air cooling to room temperature, and then keeping warm at 450°C for 3.5 hours, and then air cooling to room temperature to obtain a titanium alloy.

[0038] Example 2

[0039] A titanium alloy obtained by injection molding of titanium alloy powder;

[0040] The titanium alloy powder comprises: a TC4 titanium alloy ball and a TiB2 layer, a polyamine layer, and a graphene oxide layer sequentially coated on the surface of the TC4 titanium alloy ball, wherein the graphene oxide layer contains cerium; the average particle size of the titanium alloy powder is 20 μm;

[0041] The raw materials of TC4 titanium alloy ball include by weight percentage: Al 5.9%, V 4.1%, O 0.17%, Nd0.4%, C≤0.10, N≤0.05, H≤0.015, and the balance is Ti and unavoidable impurities;

[0042] In the process of preparing titanium alloy powder, TC4 titanium alloy ball and TiB2 are mixed at a weight ratio of 10:0.1, and ball milled at a speed of 100 rpm for 4 hours using a stainless steel ball at a ball-to-material ratio of 4:1 to obtain intermediate ball 1; intermediate ball 1 is mixed with a 1wt% triethylenetetramine aqueous solution, allowed to react at room temperature for 1 hour, taken out and washed with water to obtain intermediate ball 2; intermediate ball 2 is mixed with a 0.4wt% graphene oxide aqueous solution, allowed to stand at room temperature for electrostatic assembly for 1 hour, taken out and washed with water to obtain intermediate ball 3; intermediate ball 3 is mixed with a 0.02mol / l cerium chloride aqueous solution, allowed to stand at room temperature for electrostatic adsorption for 1 hour, taken out and washed with water, and vacuum dried to obtain titanium alloy powder.

[0043] The preparation method of the above-mentioned titanium alloy includes the following steps: taking titanium alloy powder and a binder (the formula of the binder is: 83% PW+15% LDPE+2% SA by weight percentage) and mixing them in a weight ratio of 1:1 to obtain a granular feed, and then injection molding, solvent degreasing, vacuum sintering for 2 hours in a 1100°C vacuum sintering furnace, cooling to room temperature, solutionizing at 720°C for 40 minutes, air cooling to room temperature, and then keeping warm at 470°C for 3 hours, and then air cooling to room temperature to obtain a titanium alloy.

[0044] Example 3

[0045] A titanium alloy obtained by injection molding of titanium alloy powder;

[0046] The titanium alloy powder comprises: a TC4 titanium alloy ball and a TiB2 layer, a polyamine layer, and a graphene oxide layer sequentially coated on the surface of the TC4 titanium alloy ball, wherein the graphene oxide layer contains cerium; the average particle size of the titanium alloy powder is 15 μm;

[0047] The raw materials of TC4 titanium alloy ball include by weight percentage: Al 5.9%, V 4.1%, O 0.17%, Nd0.3%, C≤0.10, N≤0.05, H≤0.015, and the balance is Ti and unavoidable impurities;

[0048] In the process of preparing titanium alloy powder, TC4 titanium alloy ball and TiB2 are mixed at a weight ratio of 10:0.07, and ball milled at a speed of 150 rpm for 3.5 hours using stainless steel balls at a ball-to-material ratio of 4:1 to obtain intermediate ball 1; intermediate ball 1 is mixed with a triethylenetetramine aqueous solution with a mass fraction of 1.5wt%, allowed to react at room temperature for 1 hour, taken out and washed with water to obtain intermediate ball 2; intermediate ball 2 is mixed with a graphene oxide aqueous solution with a mass fraction of 0.5wt%, allowed to stand at room temperature for electrostatic assembly for 1 hour, taken out and washed with water to obtain intermediate ball 3; intermediate ball 3 is mixed with a cerium chloride aqueous solution with a concentration of 0.03mol / l, allowed to stand at room temperature for electrostatic adsorption for 1 hour, taken out and washed with water, and vacuum dried to obtain titanium alloy powder.

[0049] The preparation method of the above-mentioned titanium alloy includes the following steps: taking titanium alloy powder and a binder (the formula of the binder is: 83% PW+15% LDPE+2% SA by weight percentage) and mixing them in a weight ratio of 1:1 to obtain a granular feed, and then injection molding, solvent degreasing, vacuum sintering for 2.5 hours in a 1100°C vacuum sintering furnace, cooling to room temperature, solutionizing at 710°C for 50 minutes, air cooling to room temperature, and then keeping warm at 460°C for 3 hours, and then air cooling to room temperature to obtain a titanium alloy.

[0050] Comparative Example 1

[0051] The titanium alloy powder was replaced by the intermediate ball 3 of Example 3, and the titanium alloy was prepared according to the method of Example 3.

[0052] Comparative Example 2

[0053] The titanium alloy powder was replaced by the intermediate ball 1 of Example 3, and the titanium alloy was prepared according to the method of Example 3.

[0054] Comparative Example 3

[0055] TC4 titanium alloy ball (whose formula is the same as that of Example 3) is used to replace the intermediate ball 1, and titanium alloy powder is prepared according to the method of intermediate ball 2 to titanium alloy powder in Example 3, and titanium alloy is prepared using this titanium alloy powder according to the method of Example 3.

[0056] Comparative Example 4

[0057] The TC4 titanium alloy balls of Example 3 were used to replace the titanium alloy powder, and the titanium alloy was prepared according to the method of Example 3.

[0058] The mechanical properties of the titanium alloys obtained in each group were tested by a universal testing machine. The results are shown in Table 1.

[0059] Table 1 Test results

[0060]

[0061]

[0062] It can be seen from Table 1 that the use of the titanium alloy powder with a specific structure of the present invention can improve the tensile strength of the titanium alloy while still maintaining good elongation.

[0063] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A titanium alloy, characterized in that: The titanium alloy is obtained by injection molding of titanium alloy powder; The titanium alloy powder comprises: a titanium alloy ball and a TiB2 layer, a polyamine layer and a graphene oxide layer sequentially coated on the surface of the titanium alloy ball, and the graphene oxide layer contains cerium element.

2. The titanium alloy according to claim 1, characterized in that: The titanium alloy ball is a TC4 titanium alloy ball, wherein the TC4 titanium alloy ball contains 0.2-0.4wt% of Nd.

3. The titanium alloy according to claim 1 or 2, characterized in that: The polyamine is at least one of diethylenetriamine and triethylenetetramine; preferably, the average particle size of the titanium alloy powder is 15-25 μm.

4. The titanium alloy according to any one of claims 1 to 3, characterized in that: In the process of preparing titanium alloy powder, titanium alloy balls are mixed with TiB2 and ball-milled to obtain intermediate balls 1; intermediate balls 1 are mixed with polyamine aqueous solution and allowed to react to obtain intermediate balls 2; intermediate balls 2 are mixed with graphene oxide aqueous solution and electrostatically assembled to obtain intermediate balls 3; intermediate balls 3 are mixed with an aqueous solution containing cerium ions, electrostatically adsorbed, and vacuum dried to obtain titanium alloy powder.

5. The titanium alloy according to claim 4, characterized in that: The weight ratio of titanium alloy ball to TiB2 is 10:0.05-0.1; preferably, the ball milling speed is 100-150 rpm, and the ball milling time is 3-4h.

6. The titanium alloy according to claim 4 or 5, characterized in that: The reaction was allowed to stand at room temperature for 0.5-1 h.

7. The titanium alloy according to any one of claims 4 to 6, characterized in that: The electrostatic assembly is performed at room temperature for 0.5-1 h; preferably, the electrostatic adsorption is performed at room temperature for 0.5-1 h.

8. The titanium alloy according to any one of claims 4 to 7, characterized in that: The mass fraction of the polyamine aqueous solution is 1-2wt%; preferably, the mass fraction of the graphene oxide aqueous solution is 0.4-0.6wt%.

9. The titanium alloy according to any one of claims 4 to 8, characterized in that: In the aqueous solution containing cerium ions, the concentration of cerium ions is 0.02-0.04 mol / l.

10. A method for preparing the titanium alloy according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing titanium alloy powder with a binder, injection molding, degreasing, vacuum sintering at 1000-1100°C for 2-3 hours, cooling to room temperature, solutionizing at 700-720°C for 40-60 minutes, air cooling to room temperature, heat preservation at 450-470°C for 3-3.5 hours, and air cooling to room temperature to obtain a titanium alloy.

Citation Information

Patent Citations

  • Powder surface treating agent, titanium or titanium alloy powder injection molding method and product

    CN109909497A

  • Preparation method of in-situ synthesized ceramic phase reinforced titanium matrix composite and product

    CN109971982A

  • Preparing method capable of achieving TC4 titanium alloy high toughness through co-reinforcement method

    CN111644615A

  • GNPs and TiBw synergistically reinforced titanium-based composite material and preparation method thereof

    CN114457251A

  • Preparation method of titanium carbide and titanium boride reinforced titanium-based layered composite material

    CN117867314A